Bronchiolitis obliterans in pediatric patient associated with exposure to cocaine and other abuse drugs during the gestational period (Research, Society and Development, 2021)
There is still little information in the literature about the association between exposure of pregnant women to drugs of abuse, including cocaine, and the development of bronchiolitis obliterans (BO) in the neonate. In this case report, we covered the follow-up over the years of a male pediatric patient who was admitted as a wheezing infant and who, after evaluations and observance of suggestive clinical and imaging criteria, was diagnosed with BO. Therefore, the findings of this report foster the literature and shed light on a causal relationship between exposure of pregnant women to drugs of abuse and the development of BO in the newborn, as well as on the epidemiological profile, clinical and imaging diagnosis and therapy (medications and oxygen therapy) in the course of the disease in pediatric patients and their comorbidities, also directing future strategies for the management of patients with BO.